Properties of attractive points in cat(0) spaces - K. Kunwai (2018)
© 2015 by the Mathematical Association of Thailand. All rights reserved. We study attractive points of nonlinear mappings in CAT (0) spaces. We prove the attractive point theorem for normally generalized hybrid mappings in a CAT (0) space satisfying (S) property.